Wavefront subaperture stitching with Shack-Hartmann sensor - Li, Hongru (2018)
A new approach for large field of view measurement using the Shack-Hartmann wavefront sensor (SHWS) is proposed. The object to be measured is divided into several subaperture units. Each unit is measured using the SHWS and a new algorithm is applied to stitch these units. Both theoretical principle and experimental verification are provided in this paper. A comparison between the present global optimization stitching scheme with the conventional sequential stitching method highlights the benefits of the new system. Experimental validation of the SHWS stitching algorithm is carried out by using a coated mirror. Comparison is made with a phase shifting interferometer and good agreement is found. Lastly, a new methodology for large aperture measurement of optical components is provided.